Giardia lamblia ACUTE DIARRHEA DISEASE - ELIZALDE G., GERARDO M. (2002)
OBJETIVE: To determine the pathogenicity of Giardia lamblia in relation to acute diarrhea. SETTING: Dos de Mayo National Hospital, Lima, Peru. MATERIALS AND METHODS: From 20116 coproscopies from same number of patients, we studied 57 who presented G. lamblia alone. They came mainly from Lima Department. In the fecal material we performed: 1) Stools Thevenon reaction; 2) Methilene blue and lugol staining; 3) Parasite concentration with Faust centrifugation - flotation technique; 4) Complete blood count; 5) Enterotest; 6) Radiological intestinal contrast study (intestinal transit). RESULTS: The 57 cases presented diarrhea, anorexia, epigastric pain, nausea, and weigth decrease. With methilene blue polymorphonuclear cells and/or monocytes were found in 3%. Serial stool exams (3 samples) showed over 150 cysts/gram of stools and enterotest verified vegetative and/or cystic flagelate forms. Thevenon reaction was negative. Radiologic study in 17 of 35 cases showed morphologic alterations at the duodenal-jejunum segment. Hemogram revealed moderate anemia in 45 of 57 cases. Symptomatology improved with metronidazol (26 giardiasics) and/or albendazol (31 giardiasics) treatment. CONCLUSION: Cosmopolitan flagelated Giardia lamblia is one of the causes of acute diarrhea in our population.